Distant organ metastasis patterns and prognosis of neuroendocrine cervical carcinoma: a population-based retrospective study - Li, Qing; Yu, Jie; Yi, Hanjie; Lan, Qiongyu (Frontiers in Endocrinology, 2022)
Background: Neuroendocrine carcinoma of the cervix (NECC) is a rare pathological form of cervical cancer. The prognosis of NECC with distant organ metastases is unclear. In this study, the patterns and prognosis of distant organ metastasis of NECC were investigated. Methods: Data were obtained from the surveillance epidemiology and end results (SEER) database from 2000 to 2018. Cox regression, Kaplan–Meier and log-rank analyses were conducted. Results: NECC was prone to single and multi-site metastases. The median overall survival (OS) was greatly decreased in patients with distant metastasis (P<0.0001). Other characteristics such as age ≥60 years, poorer grade, higher T stage, those without surgery, no radiotherapy, and no chemotherapy were predictors of poor prognosis. Conclusions: Metastasis is an independent prognostic factor for patients with NECC. Surgery, radiotherapy, and chemotherapy give an overall survival advantage for patients with distant organ metastases.